Perceived autonomy support, basic needs satisfaction, motivation regulation and well-being : verification of self-determination theory in dancers in Finland - Geme, Liga (2010)
Geme, L. 2010. Perceived autonomy support, basic need satisfaction, motivation regulation and well-being: Verification of self-determination theory in dancers in Finland. 2010 University of Jyväskylä. Master Thesis of Sport and Exercise Psychology. Department of Sport Sciences. 84 pages.